Multitargeting Effects of Calebin A on Malignancy of CRC Cells in Multicellular Tumor Microenvironment - Buhrmann, Constanze; Kunnumakkara, Ajaikumar B.; Kumar, Aviral; Samec, Marek; Kubatka, Peter; Aggarwal, Bharat B.; Shakibaei, Mehdi (Frontiers in Oncology, 2021)
Background Tumor microenvironment (TME) provides the essential prerequisite niche for promoting cancer progression and metastasis. Calebin A, a component of Curcuma longa, has long been investigated as a safe multitargeted agent with antitumor and anti-inflammatory properties. However, the multicellular-TME-induced malignancy and the antitumorigenic potential of Calebin A on colorectal cancer (CRC) cells in 3D-alginate cultures are not yet understood, and more in-depth research is needed. Methods 3D-alginate tumor cultures (HCT116 cells) in the multicellular proinflammatory TME (fibroblast cells/T lymphocytes), tumor necrosis factor beta (TNF-β)-TME (fibroblast cells/TNF-β) were treated with/without Calebin A to address the pleiotropic actions of Calebin A in the CRC. Results We found that Calebin A downmodulated proliferation, vitality, and migration of HCT116 cells in 3D-alginate cultures in multicellular proinflammatory TME or TNF-β-TME. In addition, Calebin A suppressed TNF-β-, similar to multicellular-TME-induced phosphorylation of nuclear factor kappa B (NF-κB) in a concentration-dependent manner. NF-κB-promoting proinflammatory mediators, associated with tumor growth and antiapoptotic molecules (i.e.,MMP-9, CXCR4, Ki-67, β1-integrin, and Caspase-3) and its translocation to the nucleus in HCT116 cells, were increased in both TME cultures. The multicellular-TME cultures further induced the survival of cancer stem cells (CSCs) (upregulation of CD133, CD44, and ALDH1). Last but not the least, Calebin A suppressed multicellular-, similar to TNF-β-TME-induced rigorous upregulation of NF-κB phosphorylation, various NF-κB-regulated gene products, CSCs activation, and survival in 3D-alginate tumor cultures. Conclusions The downmodulation of multicellular proinflammatory-, similar to TNF-β-TME-induced CRC proliferation, survival, and migration by the multitargeting agent Calebin A could be a new therapeutic strategy to suppress inflammation and CRC tumorigenesis.